Evidence of horsemanship and dogmanship and their application in veterinary contexts. Issue 3 (June 2015) - Payne, E.; Boot, M.; Starling, M.; Henshall, C.; McLean, A.; Bennett, P.; McGreevy, P.
Highlights This article reviews horsemanship and dogmanship in the veterinary sector. The arousal and affective state of the animal are useful determinants of best practice. Factors which define best practice have been identified and tabulated. Affiliation and positive reinforcement are crucial to horsemanship and dogmanship.